Enrichment of the pedagogical cluster of educational services - Ponomarova, Halyna; Kharkivska, Alla; Petrychenko, Larysa; Roganova, Maryna (My University, 2022)
Within the framework of the study, the group of authors analysed the main issues of development and enrichment of the pedagogical cluster of educational services in Ukraine and proved that the pedagogical process of professional training of future teachers in higher education institutions needs constant modernization. In accordance with modern requirements (world trends, democratic values, principles of a market economy, modern scientific and technical achievements; updating of methodological tools, expansion of innovative approaches to the training of teaching staff, etc.) and the realities of today (organization of the educational process in conditions of quarantine restrictions, martial law, etc.) new systems appear. They provide conceptual ideas, innovative theories and approaches to the strategy and main areas of improvement of national education. Therefore, the aim of the collective monograph is an analytical review of the theory and practice of education, the determination of the nature and dynamics of institutional changes in the educational paradigm in general and its individual directions or components in particular, the expansion of pedagogical experience and the enrichment of the pedagogical cluster of educational services in Ukraine. Awareness of the conclusions made in the collective monograph will contribute to the renewal of the pedagogical system of education in institutions of higher education, comprehensive development of future teachers and their digital literacy in accordance with today's conditions; will contribute to the modernization of the educational paradigm and overcoming the digital divide in the field of higher education; will contribute to an effective increase in the quality of their training, an increase in the number of competitive specialists in the market of educational services in the system of improving their qualifications, and an increase in the competitiveness of domestic institutions of higher education in the international labour market.
Enrichment of the pedagogical cluster of educational services : International collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko, M. Roganova and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Kharkiv-Praha : Oktan print, 2022. – 556 p.
Keywords: підготовка вчителів, вища освіта України, освітні послуги, модернізація; teacher training, higher education of Ukraine, educational services, modernization